Associations among self-reported diabetes, nutritional status, and socio-demographic variables in community-dwelling older adults - MORETTO, Maria Clara (2014)
ObjectiveThe aim of this study was to describe relationships between self-reported diabetes mellitus and its treatment, according to demographic and socioeconomic data, as well as indicators of nutritional status in community-dwelling older adults. MethodsThis is a population-based and a cross-sectional study derived from the multicentric survey “Frailty in Brazilian Elderly”. The random sample consisted of 881 community-dwelling older adults aged 65 years and older from the city of Campinas. The self-reported variables were: age, gender, family income (minimum salaries), education (years of education); and absolute data (yes versus no) regarding unintentional weight loss and weight gain, diabetes, and its treatment. Anthropometric variables were collected by trained examiners following classic protocols. Body mass index was classified as: underweight <23; normal weight ≥23 and <28; overweight ≥28 and <30; and obesity ≥30. Waist-to-hip ratio, indicator of abdominal adiposity, was classified according themetabolic risk, for male and female, respectively: low 0.90-0.95 and 0.80-0.85; moderate 0.96-1.00 and 0.86-0.90; and high >1.00 and >0.90. ResultsThe variables most associated with diabetes were obesity (OR=2.19), abdominal adiposity (OR=2.97), and unintentional weight loss (OR=3.38). The lack of diabetes treatment was associated with advanced age (p=0.027), lower educational level (p=0.005), and low metabolic risk (p=0.004). ConclusionSelf-reported diabetes was associated with obesity but mostly with abdominal adiposity and unintentional weight loss. Not being treated for diabetes mellitus was associated with advanced age, lower levels of education, and lower abdominal adiposity.